Computational Modeling of Polymer Composites : a Study of Creep and Environmental Effects. - Roy, Samit (CRC series in computational mechanics and applied analysis., 2013)
Computational Modeling of Polymer Composites: A Study of Creep and Environmental Effects details the development of polymeric materials and their use in smart materials and composite structures in aerospace and automotive industries. Based on the authors' work during the past 30 years, this book provides a strong understanding of the theories and associated finite element life-prediction models for elastic and viscoelastic response of polymers and polymer composites in aggressive environments. The subject is an interdisciplinary one where chemists, material scientists, and.